Menu Close

factorise-4x-4-81-




Question Number 191430 by TechnicalDev last updated on 24/Apr/23
factorise 4x^4 +81
factorise4x4+81
Answered by som(math1967) last updated on 24/Apr/23
4x^4 +81  =(2x^2 )^2 +(9)^2   =(2x^2 +9)^2 −2.2x^2 .9  =(2x^2 +9)^2 −(6x)^2   =(2x^2 +9+6x)(2x^2 +9−6x)  =(2x^2 +6x+9)(2x^2 −6x+9)
4x4+81=(2x2)2+(9)2=(2x2+9)22.2x2.9=(2x2+9)2(6x)2=(2x2+9+6x)(2x2+96x)=(2x2+6x+9)(2x26x+9)
Answered by manxsol last updated on 24/Apr/23
(2x^2 )^2 +(9)^2 +2(2x^2 )(9)−(6x)^2   (2x^2 +9)^2 −(6x)^2   fact real  (2x^2 −6x+9)(2x^2 +6x+9)  Δ=36−4(2)(9)=−36  fact complex  ((6+6i)/4)=((3+3i)/2)  (x−((3+3i)/2))(x−((3−3i)/2))(x−((−3+3i)/2))(x−((−3−3i)/2))
(2x2)2+(9)2+2(2x2)(9)(6x)2(2x2+9)2(6x)2factreal(2x26x+9)(2x2+6x+9)Δ=364(2)(9)=36factcomplex6+6i4=3+3i2(x3+3i2)(x33i2)(x3+3i2)(x33i2)
Answered by namphamduc last updated on 24/Apr/23
4x^4 +81=(2x^2 )^2 +2.2x^2 .9+81−36x^2   =(2x^2 +9)^2 −(6x)^2 =(2x^2 −6x+9)(2x^2 +6x+9)
4x4+81=(2x2)2+2.2x2.9+8136x2=(2x2+9)2(6x)2=(2x26x+9)(2x2+6x+9)

Leave a Reply

Your email address will not be published. Required fields are marked *